Neurobiological emergentism: sentience as an emergent process and the experiential gap - Feinberg, Todd E. (Frontiers in Psychology, 2025)
One of the most controversial and debated problems regarding the nature of sentience, is how to integrate the biology and neurobiology of sentience with the problem of the “explanatory gaps” that are proposed to arise between the functions of the nervous system as objectively and scientifically explained and sentience—or more generally consciousness—as it is subjectively experienced. In this paper I discuss a theory I have called Neurobiological emergentism (NBE) that is based upon a biological-neurobiological-evolutionary model that explains both how sentience emerges from complex nervous systems as well as scientifically resolves the explanatory gaps. I propose a model in which the emergence of sentience occurs roughly in three stages: Emergent Stage 1 (ES1) single-celled sensing organisms without neurons or nervous systems that appeared approximately 3.5–3.4 billion years ago and are non-sentient; Emergent Stage 2 (ES2) presentient animals that appeared approximately 570 million years ago (mya) that have neurons and simple nervous systems and fall between ES1 and ES3 animals; and Emergent stage 3 (ES3) sentient animals that emerged along diverse evolutionary lines during the Cambrian period approximately 560–520 mya, a group that includes all vertebrates (fish, reptiles, birds, and mammals), arthropods (insects and crabs), onychophorans (velvet worms) and cephalopods such as the octopus and squid that possess neurobiologically complex central nervous systems. I describe how this model leads to a scientific resolution of two related “explanatory gaps” (the personal nature of sentience and the character of experience), both of which are created by the natural emergence of sentience. However, in place of the “explanatory gaps,” I propose that there is an experiential gap that emerges between the objective brain and subjective experience, but that this “gap” can be fully scientifically explained and naturalized and can account for the personal subjective nature of sentience without completely “objectifying” it.